In Situ g-C3N4@Zno Nanocomposite: One-Pot Hydrothermal Synthesis and Photocatalytic Performance under Visible Light Irradiation. (11th May 2021) - Luu Thi, Lan Anh; Neto, Mateus Manuel; Van, Thang Pham; Nguyen Ngoc, Trung; Nguyen Thi, Tuyet Mai; Nguyen, Xuan Sang; Nguyen, Cong Tu
Abstract : In situ g-C3 N4 @ZnO nanocomposites (with 0, 1, 3, 5, and 7 wt.% of g-C3 N4 in nanocomposite) were synthesized via a one-pot hydrothermal method using precursors of urea, zinc nitrate hexahydrate, and hexamethylenetetramine. The g-C3 N4 @ZnO nanocomposites were characterized by X-ray diffraction, scanning electron microscope, diffuse reflectance spectroscopy, and photoluminescence spectroscopy. The photocatalyst activity of g-C3 N4 @ZnO nanocomposites was evaluated via methylene blue degradation experiment under visible light irradiation. The g-C3 N4 @ZnO nanocomposites showed an enhancement in photocatalytic activity in comparison to pure ZnO which increased with the g-C3 N4 content (1, 3, 5, and 7 wt.%) in nanocomposites. The photocatalytic activity reached the highest efficiency of 96.8% when the content of g-C3 N4 was 7.0 wt.%. Nanocomposite having 7.0 wt.% of g-C3 N4 also showed good recyclability with degradation efficiency higher than 90% even in the 4 th use. The improvement of photocatalytic activity could be attributed to the adsorption ability and effective separation of electron-hole pairs between g-C3 N4 and ZnO. This work implies a simple method to in situ prepare the nanocomposite material of g-C3 N4 and semiconductors oxide for photocatalyst applications with high efficiency and good recyclability.